Thermal Simulation and Experiment of Lunar Drill Bit in Vacuum - Jinsheng Cui; Xuyan Hou; Deming Zhao; Yousong Hou; Qiquan Quan; Xiang Wu; Zongquan Deng; Shengyuan Jiang; Dewei Tang (Institute of Advanced Engineering and Science, 2014)
Drilling samples of lunar soil is an important and indispensable part of China’s lunar exploration project. The drill bit temperature during the drilling process is one of the key concerns for scholars, especially for the hard lunar rock drilling in vacuum. In this article, the simulation analysis of drilling in atmosphere and vacuum is conducted. Moreover, a fiber grating temperature measuring system integrated with vacuum drilling system is established. Experiment on lunar rock stimulant in atmosphere and vacuum is taken out and compared. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5496